THE SOCISAL INVOLVEMENT AS THE CONSTITUENT OF NATURALISM’S RESEARCH IN V. VYNNYCHENKO’S LITERARY WORKS - Kobzey, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the process of evolution of V. Vynnychenko’s political consciousness is being invented. It was under the influence of certain sociological doctrine but still remains an adapter of the biophysical motivation of the individual’s behaviour? Which was set up not on the theory of society class struggle but on the realiaing the importance of primordial instincts in the process of forming an individual personality